Economics of Block Chain and the Money Market Equilibrium - R. Pazhanisamy; E. Selvarajan (Department of Humanities and Social Sciences (HSS), Jain University Global Campus, 2021)
The overwhelming public response towards the crypto currencies like Bitcoin, Ethorium has gained serious attention among the researchers and policy makers around the various countries. The rationale behind the claim of dis-intermediary of financial system and the low transaction cost effective nature coupled with the absence of the agency problems in the financial market creates an illusion among public to take part and attempt to speculate in it. The reviews of literature on the themes of the economics of the block chain technology used in the cryptos shows that there are high degree of uncertainties of the nature and the impact it create due to the absence regulations both partial and absolute terms on the one hand, the absence of theoretical, empirical, conceptual an methodological clarity from the economic theories on the other hand calls for an enquiry into the crypto's usefulness at the gross root levels for which this present attempt is made. Using a set of realistic assumptions a conceptual framework is prepared and the future of the money market equilibrium is predicted. In the lights of the changes in the money market equilibrium with response to the changes in the crypto currencies it is found that in the long run there will be negative impact on the economy certainly which leads to the collapse the global economics if it is unnoticed to implement necessary policy adjustments at the national and global levels collectively.
Keywords: G15; G32; E42; E51; E58; F30; L51; 330; Block Chain Economics; Crypto Currency; Money Market Equilibrium; Economics of blockchain